1994
DOI: 10.1183/09031936.94.07030459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an inhaled neutral endopeptidase inhibitor, thiorphan, on airway responsiveness to leukotriene D4 in normal and asthmatic subjects

Abstract: Cysteinyl leukotrienes are potent inflammatory mediators that are considered to play a role in the pathophysiology of asthma. It can be postulated that leukotrienes exert their bronchoconstricting effects, in part, through secondary release of endogenous neuropeptides. We examined the effect of inhaled thiorphan, an inhibitor of a neuropeptide degrading enzyme, on the concentration-response curve to leukotriene D4 (LTD4) in a two-period, double-blind, cross-over and placebo-controlled study, in 16 nonasthmatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
(92 reference statements)
1
10
0
Order By: Relevance
“…However, NK 2 -receptor antagonist, SR 48968, significantly inhibited the LTD 4 -induced RL elevation. These results are in keeping with observations in humans in vivo, showing a slight increase in maximal bronchoconstriction to LTD 4 following pretreatment with an inhibitor (thiorphan) or tachykinin-degrading enzyme, neutral endopeptidase [36]. Because tachykinins have been reported to cause airway smooth muscle contraction via NK 2 -receptors [6,27], the LTD 4 -induced RL elevation observed in the present study seems to be due to the airway smooth muscle contraction rather than airway plasma leakage and subsequent airway wall oedema.…”
Section: Discussionsupporting
confidence: 79%
“…However, NK 2 -receptor antagonist, SR 48968, significantly inhibited the LTD 4 -induced RL elevation. These results are in keeping with observations in humans in vivo, showing a slight increase in maximal bronchoconstriction to LTD 4 following pretreatment with an inhibitor (thiorphan) or tachykinin-degrading enzyme, neutral endopeptidase [36]. Because tachykinins have been reported to cause airway smooth muscle contraction via NK 2 -receptors [6,27], the LTD 4 -induced RL elevation observed in the present study seems to be due to the airway smooth muscle contraction rather than airway plasma leakage and subsequent airway wall oedema.…”
Section: Discussionsupporting
confidence: 79%
“…And finally, the present dose and dosing intervals of thiorphan administration were derived from previous observations, as was pointed out in the method section [6.8,18,19,24]. Throughout the allergen challenge, the cumulative dose of thiorphan was twice the dose which has been shown to enhance the bronchoconstrictor response to inhaled neurokinin A in non-asthmatic and mildly asthmatic humans [6,8] and to leukotriene D4 [18] and metabisulfite [19] in nonasthmatics. Since potentiation of the latter two challenges can be considered to be due to the reduced breakdown of endogenous neuropeptides, it seems likely that the present dose of thiorphan would have been sufficient to inhibit the cleavage of neuropeptides that are released secondary to allergen challenge.…”
Section: Discussionmentioning
confidence: 99%
“…maximal potentiation ofthe bronchoconstrictor response to exogenous NKA in asthmatic subjects [6]. Furthermore, without affecting the airway response to methacholine in asthmatics [6], 1.25 mg of inhaled thiorphan significantly enhanced the maximal response plateau to other pro-inflammatory stimuli, such as inhaled LTD4 [18] and metabisulfite [19] in non-asthmatic humans. Although in a pharmacokinetic study in guineapigs, inhaled thiorphan has been shown to possess a short duration of action (± 5 min) in potentiating the effect to inhaled SP [24], in previous studies in non-asthmatic subjects, we have shown that 1.25 mg of inhaled thiorphan has enhanced the maximum airway narrowing to inhaled NKA or LTD4 for at least ijh [8,18].…”
Section: Thiorphanmentioning
confidence: 95%
See 2 more Smart Citations